Consensus statement on blocking the effects of interleukin-6 and in particular by interleukin-6 receptor inhibition in rheumatoid arthritis and other inflammatory conditions. Issue 4 (21st November 2012) - Smolen, Josef S; Schoels, Monika M; Nishimoto, Norihiro; Breedveld, Ferdinand C; Burmester, Gerd R; Dougados, Maxime; Emery, Paul; Ferraccioli, Gianfranco; Gabay, Cem; Gibofsky, Allan; Gomez-Reino, Juan Jesus; Jones, Graeme; et al.
Abstract : Background: Since approval of tocilizumab (TCZ) for treatment of rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA), interleukin 6 (IL-6) pathway inhibition was evaluated in trials of TCZ and other agents targeting the IL-6 receptor and ligand in various RA populations and other inflammatory diseases. This consensus document informs on interference with the IL-6 pathway based on evidence and expert opinion. Methods: Preparation of this document involved international experts in RA treatment and RA patients. A systematic literature search was performed that focused on TCZ and other IL6-pathway inhibitors in RA and other diseases. Subsequently, incorporating available published evidence and expert opinion, the steering committee and a broader expert committee (both including RA patients) formulated the current consensus statement. Results: The consensus statement covers use of TCZ as combination- or monotherapy in various RA populations and includes clinical, functional and structural aspects. The statement also addresses the second approved indication in Europe JIA and non-approved indications. Also early phase trials involving additional agents that target the IL-6 receptor or IL-6 were evaluated. Safety concerns, including haematological, hepatic and metabolic issues as well as infections, are addressed likewise. Conclusions: The consensus statement identifies points to consider when using TCZ, regarding indications, contraindications, screening, dose, comedication, response evaluation and safety. The document is aimed at supporting clinicians and informing patients, administrators and payers on opportunities and limitations of IL-6 pathway inhibition.